Apoptotic extracellular vesicles alleviate Pg‐LPS induced inflammatory responses of macrophages via AMPK/SIRT1/NF‐κB pathway and inhibit osteoclast formation. Issue 11 (4th August 2022) - Ye, Qingyuan; Xu, Haokun; Liu, Shiyu; Li, Zihan; Zhou, Jun; Ding, Feng; Zhang, Xige; Wang, Yazheng; Jin, Yan; Wang, Qintao
Abstract: Background: Periodontitis is caused by the imbalance of anti‐bacteria immune response and excessive inflammation whereas macrophages play an important role in inflammation. Thus, it is critical for finding efficient anti‐inflammatory strategies to alleviate periodontal inflammation and prevent bone destruction. Apoptosis of mesenchymal stem cells (MSCs) exerts immune silencing effects, however, using these effects to develop anti‐inflammatory strategies remains unknown. In our study, we extracted apoptotic extracellular vesicles (ApoEVs) from bone marrow MSCs (BMMSCs) and found ApoEVs inhibited macrophages polarizing into proinflammatory condition via AMPK/SIRT1/NF‐κB pathway. Besides that, we also found ApoEVs inhibited adjacent osteoclast formation by suppressing the secretion of TNF‐α of proinflammatory macrophages. Methods: BMMSCs derived ApoEVs were extracted by gradient centrifugation. Protein expression level and secreted cytokines of ApoEVs treated macrophages were examined by western blot and ELISA, respectively. Besides, the change of NF‐κB pathway and related molecules were examined by immunofluorescence and western blot. The osteoclast formation under the different conditioned mediums from macrophages was measured by TRAP staining, MMP‐9 expression, and pit assay. Results: ApoEVs were extracted from staurosporine‐induced apoptotic BMMSCs and were in sphere shapes whose diameters are between 100 and 1000 nm. ApoEVs could be phagocyted by macrophages and in turn reduce the expression of COX2 in proinflammatory macrophages. Besides that, ApoEVs suppressed the secretions of TNF‐α and IL‐6 while elevating the secretion of IL‐10 in a dose‐dependent manner. Further studies revealed that ApoEVs inhibited macrophages polarizing into proinflammatory phenotypes via AMPK/SIRT1/NF‐κB pathway. In addition, ApoEVs inhibited osteoclasts differentiation and bone resorption measured by TRAP staining, MMP‐9 expression, and pit resorption area by downregulating the secretion of TNF‐α of proinflammatory macrophages. Conclusions: The results suggest that ApoEVs inhibited macrophages to skew into proinflammatory phenotypes via AMPK/SIRT1/NF‐κB pathway and suppress adjacent osteoclasts formation by reducing the secretion of TNF‐α. Our findings shed a light on the treatment for periodontitis based on EVs therapy.